2020
DOI: 10.1002/met.1953
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and meningitis under climate change: initial assessment of climate information service in Nigeria

Abstract: It is often difficult to define the relationship and the influence of climate on the occurrence and distribution of disease. To examine this issue, the effects of climate indices on the distributions of malaria and meningitis in Nigeria were assessed over space and time. The main purpose of the study was to evaluate the relationships between climatic variables and the prevalence of malaria and meningitis, and develop an early warning system for predicting the prevalence of malaria and meningitis as the climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Malaria incidence varied from 76 % during the rainy season to 24 % during the dry season. Ayanlade et al, (2020) observed a significant positive relationship between rainfall and malaria, especially during the wet season with correlation coefficient R 2 ≥ 60.0 in almost all the ecological zones of Nigeria. In the Sahel, Sudan and Guinea savannah, a strong relationship between temperature and meningitis was observed with R 2 > 60.0.…”
Section: Introductionmentioning
confidence: 87%
“…Malaria incidence varied from 76 % during the rainy season to 24 % during the dry season. Ayanlade et al, (2020) observed a significant positive relationship between rainfall and malaria, especially during the wet season with correlation coefficient R 2 ≥ 60.0 in almost all the ecological zones of Nigeria. In the Sahel, Sudan and Guinea savannah, a strong relationship between temperature and meningitis was observed with R 2 > 60.0.…”
Section: Introductionmentioning
confidence: 87%
“…Meningococcal meningitis (CSM) is defined as an acute bacterial disease with fever, severe headache, nausea, and stiff neck [1]. Meningitis is one of the most important causes of morbidity and death in African [2]. The challenges of meningitis and climate relationship is now an issue of concern worldwide.…”
Section: Background To the Studymentioning
confidence: 99%
“…( 2017 ) and Ayanlade et al. ( 2020 ) found that high temperatures were a significant risk factor for meningitis in Niger and Nigeria. Overall, these studies showed that atmospheric factors like dust, Harmattan winds, temperature, and humidity may impact the seasonality of meningitis in West Africa.…”
Section: Introductionmentioning
confidence: 98%
“…Pandya et al (2015) found that an average of 40% relative humidity or greater for several weeks would naturally end a meningitis epidemic with no vaccine. Jusot et al (2017) and Ayanlade et al (2020) found that high temperatures were a significant risk factor for meningitis in Niger and Nigeria. Overall, these studies showed that atmospheric factors like dust, Harmattan winds, temperature, and humidity may impact the seasonality of meningitis in West Africa.…”
mentioning
confidence: 99%